Analysis of the precision sustainability of the preload double-nut ball screw with consideration of the raceway wear. (September 2020) - Zhao, Jiajia; Lin, Mingxing; Song, Xianchun; Guo, Qizhen
Ball screws are the driving components used to convert the rotational motion into linear motion in precision equipment. However, the machining accuracy of precision equipment is directly determined by the positioning accuracy of the ball screw. The authors analyze the precision sustainability of preload double-nut ball screws with raceway wear. A new wear model combining the modified Archard theory and the iterative interpolation method is established to analyze the variations in wear depth. A new model considering the coupling relationship between raceway wear and preload loss is proposed to study the precision life of the double-nut ball screw. In addition, a novel running test bench is designed to verify the precision sustainability of ball screws. The precision sustainability of the ball screw is analyzed during its life cycle, and these results match the theoretical values obtained by using the wear model.